Clostridium butyricum potentially improves inflammation and immunity through alteration of the microbiota and metabolism of gastric cancer patients after gastrectomy - Cao, Wenjie; Zheng, Cihua; Xu, Xuan; Jin, Rui; Huang, Feng; Shi, Meng; He, Zhipeng; Luo, Yufeng; Liu, Lulin; Liu, Zhaoxia; Wei, Jing; Deng, Xiaorong; et al. (Frontiers in Immunology, 2022)
Background: Gastrectomy is the most effective treatment to improve the clinical survival rate of patients with gastric cancer. However, the pathophysiological changes caused by gastrectomy have seriously affected the postoperative recovery. Methods: In the present study, Ataining (containing C. butyricum, CGMCC0313.1) was used after gastrectomy to investigate the effect of C. butyricum on the early postoperative recovery by monitoring the inflammatory immune response with blood indicators, detecting the gut microbiota with high-throughput sequencing, and analyzing the short-chain fatty acids (SCFAs) with targeted metabolomics. This study is registered with the number ChiCTR2000040915. Results: Our outcomes revealed C. butyricum could reduce early postoperative inflammation (P < 0.001), enhance immunity (P < 0.001), improve postoperative nutritional status (P < 0.01) and reduce the occurrence of postoperative complications. In addition, the use of the C. butyricum greatly enriched the relative abundance of beneficial bacteria Bacteroides, Faecalibacterium and Gemmiger, while markedly decreased the abundance of pathogenic Streptococcus, Desulfovibrio and Actinomyces at genus level. We also observed significant up-regulation of SCFAs, including acetic acid, propionic acid, butyric acid and isobutyric acid, after gastrectomy for C. butyricum. Conclusion: Therefore, we believe that oral administration of C. butyricum after gastrectomy can reduce early postoperative inflammation, enhance immune ability, restore intestinal microecological balance, increase intestinal SCFAs, reduce the occurrence of postoperative complications, and ultimately promote the early recovery of the patient.